Clinicopathological Study on TB Lymphadenopathy Case (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2021)
Background: Tuberculosis in the form of pulmonary and extrapulmonary TB is common in developing countries like Bangladesh. Among extrapulmonary TB, lymphnode TB is still common in our setting. So, the objectives of the present study were to evaluate theclinicopathological findings among the lymphnode TB cases in our context.Materials and methods: This observational study was done from January 2017 to December 2019 among 300 lymphnode TB cases in a tertiary care hospital during a three-year study period. Patients were selected after obtaining informed written consent and clinical evaluation. Then enlarged lymphnodes were evaluated by FNAC or histopathology. If lymphnode TB features were found then the patients were included in our study.Other findings like metastasis, lymphoma or pyogenic lymphadenitis were excluded from this study. After collection, data was recorded and analyzed by Microsoft Excel.Results: Among 300 cases of TB lymphadenitis subjects were commonly within the age groups 11-20 years (Male 63 and female 51) and 21-30 years(male 45 and female 42) with amale: female ratioof 1.22:1. Regarding different clinical signs and symptoms,low grade fever was found in 21(7%) cases, local lymphnode pain and tenderness was found in 67 (22%) and 63(21%) of subjects. Discharging sinuses was present in 33(11%) patients, 35(12%) had history of weight loss, 39 (13%) had anorexia and 42(14%) had history of night sweats. Regarding locationof different lymph node areas, 125(41.67%) patients had deep cervical nodes, 65(21.67%) had supraclavicular lymph nodes, 60(20%) had lymph nodes in the posterior triangle 33 (11%) in jugulo-omohyoid and 17 (5.66%) in submandibular area. Among all cases, 83% cases showed bilateral and 17% showed unilateral involvement.Regarding nature of lymph nodes, firm, matted multiple lymphnodes were found in 130(43%) cases, single discrete nodes were found in 70(23.33%) cases, others were found as suppurative noded with single and multiple sinuses. Cytopathological and histopathological findings revealed caseating granuloma with epithelioid cell with Langerhans type giant cell was found in 220(73%) cases, caseating granuloma with epithelioid cell was found in 47(16%) epithelioid cell was found in 20(7%) cases and epitheliod cells with smear positive AFB was found in 13(4%) cases.Conclusion: TB lymphadenitis is still a common form of extrapulmonary tuberculosis and it has variable clinical and pathological presentations.Chatt Maa Shi Hosp Med Coll J; Vol.20 (1); January 2021; Page 77-80